Common Values and the Coase Conjecture: Inefficiencies in Frictionless Contract (Re-)Negotiation - Vitali Gretschko; Achim Wambach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We consider the contracting problem of a principal who faces an agent with private information and cannot commit to not renegotiate a chosen contract. To analyze this problem, we propose an infinite horizon negotiation protocol in which renegotiation is frictionless, executed without delay and there are no restrictions on how many times the contracts can be renegotiated. We provide a general characterization of renegotiation-proof outcomes and show that those outcomes are supported by a Perfect Bayesian Equilibrium of the negotiation game. The general characterization of renegotiation-proof outcomes provides a powerful and simple to use tool for finding such outcomes in specific environments. Thus, we proceed by applying the results to adverse selection environments with private and common values. We show that with private values and common values of the 'Spence' type only fully efficient and separating contracts can be renegotiation proof. However, with common values of the 'Rothschild-Stiglitz' type inefficient and (partial) pooling contracts may constitute renegotiation-proof outcomes.
Keywords: C73; C78; D82; 330